Labor Participation – A Way to Industrial Democracy - Barkin, Solomon (Relations industrielles / Industrial Relations, 1978)
The author examines the role and forms of industrial democracy in the enterprise and when in the process of selection of questions, study and analysis, search for solutions and defining the final decision and which methods of implementation shall employees and their union share, and in what manner, the responsibilities of decision-making with management. Current arrangements must be viewed essentially as transitional accommodations in the unending search for viable, more satisfying and productive plans.